LAJU INFEKSI PHYTOPHTHORA PALMIVORA PADA TANAMAN KAKAO DI DESA PULUKAN, JEMBRANA - SUDARMA, I MADE (AGRITROP; Vol. 24, No. 2 Juni 2005, 2012)
The aim of the research are to know infection rate of P. palmivora, relationship between height of fruits, age of fruits and disease intensity. Field experiment was carried out at Pulukan, Jembrana, started from November 2001 to January 2002. The observation were done to disease intensity and infection rate of P. palmivora that accured naturally by a weekly observation on 20 plants samples from 120 plants (40 are) of reasearch. The disease intensity in relation with height of fruits and age of fruits were analysed by using correlational method. The result of this experiment showed that epidemic of disease was developed as sigmoid curve. Infection rate maximum, 0,077 per unit per day on young fruits age one month. The height and age of fruits factors influenced development of disease. Relationship between height fruits from soil and disease intensity as, Y = 21,089 – 4,671 X1 (r = - 0,679**, r2 = 46 %, X1 = height fruit from soil) and relationship between age of fruit and disease intensity is Y = 20,257 – 4,339 X2 (r = -0,658**, r2 = 43 %, X2 = age of fruit).
Keywords: Epidemic, pod rot disease, P. palmivora and Cacao.